Medicines that reduce morbimortality in patients with heart failure: A literature review (Research, Society and Development, 2024)
The Heart failure (HF) is a condition characterized by the heart's inability to pump or accommodate blood efficiently, leading to symptoms resulting from decreased cardiac output and elevated filling pressures. Its treatment aims to alleviate symptoms, improve quality of life, address the underlying cause, and reduce morbidity and mortality. HF-related mortality is significant, around 50% within 5 years, along with high rates of hospitalization and readmission. Given the significant morbidity and mortality associated with heart failure, the aim of this study was precisely to conduct an integrated review of available databases to better explore the theme of which drugs used in its therapeutic arsenal are capable of reducing its morbidity and mortality and by what mechanisms this occurs. Recent studies have investigated the impact of available medications in managing HF, highlighting the effectiveness of SGLT2 co-transporter inhibitors, beta-blockers, renin-angiotensin-aldosterone system blockers, and neprilysin inhibitors and angiotensin receptor blockers in reducing morbidity and mortality. The synergy between these classes of medications, individualization of treatment, and continuous education of healthcare professionals on the subject are essential to optimize clinical outcomes and increase survival in these HF patients.